"You are Irish—and as Irish as Me!": Antiracism and National Identities in Ireland. (January 2022) - Sambaraju, Rahul
What is the role of national identities in doing antiracism? In social psychology, much research on racism has examined processes and practices of exclusion. Scant research however has examined practices of inclusion. In this paper, I examine practices of national majority group members doing antiracism in response to complaints by ethnic minority members about facing racism on Twitter about their national belonging. I examine these instances and responses to these in the Irish context, as in Ireland, being "Irish" can mean both ethnic and national identity. Findings show that respondents' national identification was central to practices of inclusion, such as that of affirming the Irishness of those facing exclusion. For respondents' national belonging was oriented to as significant for those complaining about inclusion, for themselves, and for those who were engaging in racist exclusion of ethnic minority members. Together the findings show that while national identities allow for antiracism, these problematically suppress the relevance of race in favor of nations and nationalisms.